Bilateral cataract extraction in one session: report on five years' experience. Issue 10 (October 1977) - Joseph, N.; David, R.
Abstract : Six hundred and seventy-six patients had both their cataracts removed in one operating session because of the rural and economic conditions of Malawi. These operations were performed over a period of 5 years. The final visual results were satisfactory and the number of complications acceptable in relation to the environmental conditions and medical facilities available. However, the incidence of infection is higher than would be acceptable in a sophisticated medical environment. Three eyes were lost owing to infection, but fortunately in all 3 cases the fellow eye was not affected. Furthermore, broken capsule and vitreous loss occurred more frequently than expected in a sophisticated facility in the eye first operated on. This allowed measures to be taken by the surgeon in many cases to prevent these complications from recurring in the second eye.